THE PORTRAIT OF TEACHING ENGLISH IN PRIMARY SCHOOL UNDER KURIKULUM MERDEKA: TEACHERS’ VOICES - Irfan Fajrul Falah; Rita Kusumah; Yanuarti Apsari; Agatha Kristi Pramudika Sari (Universitas Wiralodra, 2024)
The changes in the national curriculum in Indonesia have been regular since the independence. It is an action taken to improve the quality of education given the demands of both era and society as well as a preparation of more competitive outcomes. This study concerns teachers' perceptions of the current curriculum (Kurikulum Merdeka). It is important to see how it is going in the practical field, particularly in teaching English in primary schools. This study employed a case study design where Six English teachers from six different schools in Kuningan, West Java, Indonesia took part as participants in the current study. They were interviewed in two modes, onsite and online, to share their views regarding the Merdeka curriculum implementation. The data from the interviews were analyzed through qualitative analysis. The result shows that both schools and policymakers have done several aspects regarding the implementation. Meanwhile, along with its implementation, the challenges exist including time allotment, students’ proficiency, and students' motivation, Therefore, the findings should be taken seriously, to improve the quality of teaching English at the primary level.